International Programme for the Development of Communication : a decade of infancy. - ENGSTROM, Judith A. (1992)
Discusses the programme whose main purpose is to 'increase cooperation and assistance for the development of communication infrastructure, and to reduce the gap between various countries in the communication field'. Evaluates the working methods of the programme, and makes recommendations for future research.